Evaluation of Bleeding Resistance in Chip Seal and Asphalt Emulsion Residue Rheology - Preeda Chaturabong (My University, 2019)
Chip seal bleeding is influenced by many factors, including design inputs, material properties, and project-specific conditions. It reduces the surface texture of the pavement and thus compromises the safety of the traveling public. Even though factors that bring about premature bleeding are known, currently, no laboratory test methods for evaluating bleeding in chip seals have been specified. The objective of this paper is to present the results of an investigation of the influence factors of asphalt emulsion residue properties measured by the ASTM D7405 multiple stress creep and recovery (MSCR) test, as well as other factors related to chip seal bleeding resistance as measured by the modified loaded wheel test (MLWT). In this study, the MSCR test was used as a tool for evaluating the performance of asphalt emulsions because it has been identified as a potential test related to bleeding in the field. In addition, MLWT was selected as a tool for evaluating chip seal bleeding performance in the laboratory. The results of the MLWT showed that the emulsion application rate (EAR), aggregate gradation, and emulsion properties were significant factors affecting bleeding. The MSCR test was found to be a promising tool for the performance evaluation of asphalt emulsion residue, as the test was able to differentiate between emulsion chemistries and modifications in terms of sensitivity to both temperature and stress. In relation to chip seal bleeding resistance, only the creep compliance (Jnr) obtained from the MSCR test results was identified as a significant property affecting potential for bleeding.
Keywords: Gradation; Asphalt Pavement Performance Evaluation